MOVEMENT ANALYSIS GOLD PRICE DURING COVID-19 YEARS 2020 - 2021 - Yuniarsih, Nia; Permatasari, Anita (Universitas 17 Agustus 1945 Surabaya, 2023)
Gold is a type of investment instrument that can be used as an alternative choice for investors and can be used as one of the portfolio diversification strategies. One of the considerations in investment activities in the capital market is the rate of return of the investment instrument. The ups and downs of gold price movements in this study are influenced by three factors, namely the rupiah exchange rate against the USD, inflation and the Indonesian Interest Rate (SBI), which we now know better as BI 7-day. The BI rate or BI 7-day has a function as a suppressor of the inflation rate so that economic conditions are maintained. The research design is in the form of quantitative research using secondary data while the research design used is a causal design and uses a Static tical Package for Social Sciences (SPSS) for data processing. The results of the first study show that there is an influence between the Rupiah exchange rate and the USD affecting the movement of gold during Covid-19 in 2020-2021. The results of the second study show that there is an influence between inflation affecting the movement of gold during Covid -19 in 2020-2021. The results of the third study show that there is no influence between BI 7-day on the movement of gold during Covid-19 in 2020-2021.